Live small‐animal X‐ray lung velocimetry and lung micro‐tomography at the Australian Synchrotron Imaging and Medical Beamline. (7th June 2015) - Murrie, Rhiannon P.; Morgan, Kaye S.; Maksimenko, Anton; Fouras, Andreas; Paganin, David M.; Hall, Chris; Siu, Karen K. W.; Parsons, David W.; Donnelley, Martin
<x xml:space="preserve">Abstract</x> The high flux and coherence produced at long synchrotron beamlines makes them well suited to performing phase‐contrast X‐ray imaging of the airways and lungs of live small animals. Here, findings of the first live‐animal imaging on the Imaging and Medical Beamline (IMBL) at the Australian Synchrotron are reported, demonstrating the feasibility of performing dynamic lung motion measurement and high‐resolution micro‐tomography. Live anaesthetized mice were imaged using 30 keV monochromatic X‐rays at a range of sample‐to‐detector propagation distances. A frame rate of 100 frames s−1 allowed lung motion to be determined using X‐ray velocimetry. A separate group of humanely killed mice and rats were imaged by computed tomography at high resolution. Images were reconstructed and rendered to demonstrate the capacity for detailed, user‐directed display of relevant respiratory anatomy. The ability to perform X‐ray velocimetry on live mice at the IMBL was successfully demonstrated. High‐quality renderings of the head and lungs visualized both large structures and fine details of the nasal and respiratory anatomy. The effect of sample‐to‐detector propagation distance on contrast and resolution was also investigated, demonstrating that soft tissue contrast increases, and resolution decreases, with increasing propagation distance. This new capability to perform live‐animal imaging and high‐resolution micro‐tomography at the IMBL enhances the capability for investigation of respiratory diseases and the acceleration of treatment development in Australia.